Semi-continuous regime for continuous hydrogen production from sodium borohydride methanolytic dehydrogenation - Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
With the objective of continuous H-2 production from sodium borohydride (NaBH4), methanolytic dehydrogenation has been studied and semi-continuous regimes were evaluated for making H-2 production continuous. Batch catalytic hydrogen generation profiles, with kinetic evaluation at different temperatures, were examined. The batch production experiments showed that H-2 production at 40 degrees C reached almost 100% conversion of NaBH4 after 6.5 and 6.1 min for Co-O and Co-O-B catalyzed reactions, respectively. In addition to this, a figure of merit (FOM) was performed for a comparative analysis of the catalysts' performance. The semi-continuous regime was achieved by the sequential feeding of NaBH4 into the reactor, with continuous and stable hydrogen production. It resulted in continuous H-2 production of 0.94 Lh(-1) for almost 2.6 h from Co-O-B catalyzed methanolytic dehydrogenation of NaBH4. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Semi-continuous; Sodium borohydride; Methanolysis; Hydrogen; Figure of merit; CATALYTIC-ACTIVITY; AMMONIA BORANE; CO-B; HYDROLYSIS; COBALT; GENERATION; NABH4; ALCOHOLYSIS; CU; Chemistry; Crystallography